Identity of an Islamic Ideological State: An Analytical Study - Hoque, Muhammad Rafiqul (IIUC Studies, 2012)
The Islamic system of state established by the Prophet (SM), existed from 623CE in Medina. The state of Medina was neither monarchic nor republican, ruled on the policy of the majority. This state was based neither on tribalism nor on nationalism, rather on humanism and Islamic monotheism. It was really an Ideological state and the ideology was Islam. In the present paper, an attempt has been made to describe the main features of an Islamic Ideological state through its main principles and distinguishing points of three basic organs and to analyse the differences between an Islamic state and secular states. DOI: http://dx.doi.org/10.3329/iiucs.v7i0.12266 IIUC Studies Vol.7 2011: 147-178